EMPLOYEE ENGAGEMENT DITINJAU DARI PERCEIVED ORGANIZATIONAL SUPPORT PADA KARYAWAN - Evelyn Nathalia; Tanisha Rajkaur; Raina Ananta Christien; Lycha Rosiani Br Sinulingga; Sri Hartini; Mukhaira El Akmal (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
The purpose of this research was to analyze the association between employee engagement and perceived organizational support within the employee population. The study employed a purposive sampling method, involving a total of 99 participants as both the population and sample. Data collection was conducted using a Likert-type scale to measure participant responses. To analyze the data, both the Pearson Product-Moment Correlation and additional statistical techniques were utilized with the assistance of SPSS version 25.0 for Windows. The results of the hypothesis testing revealed a strong positive relationship exists between perceived organizational support and employee engagement, as indicated by the correlation coefficient (r = 0.815) and significance level (p = 0.000; p < 0.05). These findings suggest that an increase in employee engagement is generally associated with a higher perception of organizational support, and conversely, lower engagement tends to align with reduced perceived support.